Eskalasi Kebencian Terhadap Yahudi dalam Hadis: Tinjauan Hermeneutika Double Movement - Muhammad Asgar Muzakki (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2025)
This article examines the escalation of conflict between the Muslim and Jewish communities during the Prophet Muhammad’s era through three main phases: theological conflict, betrayal, and the escalation of expulsions. Using Fazlur Rahman’s double-movement hermeneutics, this study highlights the socio-historical context underlying hadiths that are often perceived as supporting hatred toward Jews. The theological conflict is explained as Islam’s effort to strengthen its identity as an independent religion amidst the prevailing culture of abrogating previous teachings. The betrayal phase is analyzed as a response to actual threats from certain Jewish groups that violated political treaties. Meanwhile, the expulsions and raids in the final phase are understood as the culmination of a long-standing escalation. In the second movement of hermeneutics, these hadiths are reinterpreted to emphasize that the Prophet’s actions were primarily driven by political pragmatism and the security needs of a vulnerable Muslim community, rather than racial or religious hatred. This deconstruction opens space for a more inclusive reading, positioning the hadiths as products of complex historical situations. Therefore, this study aims to provide a balanced perspective in understanding conflict-related hadiths and to prevent the misuse of religious texts to justify hatred in the modern era.